Analysis of the Effectiveness of Peer-Assisted and Teacher-Centered Instruction on Mathematics Performance and Resilience in Learning Mathematics - Masoomifard, Marjan; Masoomifard, Mahsa; Nouri, Ziba; Shayestehfar, Abbas (Assessment and Practice in Educational Sciences, 2024)
The present study aimed to compare the effects of peer-assisted instruction and teacher-centered instruction on mathematics performance and resilience in learning mathematics. In terms of purpose, this research was applied; in terms of nature, it employed a quasi-experimental pretest–posttest design; and in terms of implementation, it was conducted using a survey approach. The statistical population consisted of all fifth-grade female elementary school students in District 7 of Tehran during the 2021–2022 academic year. Participants were selected through multistage cluster random sampling. Two classes were chosen as the research sample, with 30 students in each class. In one class, mathematics was taught using the peer-assisted (collaborative) instructional method, while in the other class, mathematics was taught using the teacher-centered (traditional) instructional method. Data collection instruments included a standardized mathematics achievement test to assess the learning variable and the Mathematics Resilience Scale developed by Kooken et al. (2016) to measure resilience in learning mathematics. The validity and reliability of both instruments were examined and confirmed. The results of the analysis of covariance (ANCOVA) indicated that the peer-assisted instructional method had a significant effect on mathematics performance and resilience in learning mathematics among fifth-grade elementary school students.